Augmented Reality-Based Learning in Science Education to Enhance Conceptual Understanding, Spatial Ability, and Scientific Literacy - Utami, Ayu Rischi (Scientica Education Journal, 2025)
This study aims to investigate the effectiveness of augmented reality (AR)-based learning in enhancing students’ conceptual understanding, spatial ability, and scientific literacy in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using AR-based learning integrated with inquiry-based activities and a control group taught using conventional methods. Data were collected through a conceptual understanding test, a spatial ability test, and a scientific literacy test. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, AR-based learning significantly improved students’ ability to visualize abstract concepts, interpret spatial relationships, analyze data, and apply scientific knowledge. These findings suggest that augmented reality is an effective and innovative instructional strategy for promoting meaningful learning and developing essential competencies in science education